Fatal pauses : stuck in pause and getting unstuck through the power of no and the power of go - Yudofsky, Stuart C. (American Psychiatric Publishing, Inc., 2015)
This is a fresh and fascinating take on what it means to be ""stuck"" and how to get ""unstuck."" Part textbook for mental health professionals and part self-help manual, this book guides readers through the various manifestations of this condition by presenting and analyzing the case studies of patients